ANALYSIS OF CONSUMER ATTITUDE TOWARD BRAND EXTENSION OF PRENAGEN - Kressy Arba Yuniar; Lukman Hakim; Wakhid Slamet Ciptono (Faculty of Pharmacy, Universitas Gadjah Mada)
Good brand will provide quality assurance for the company, because brand is not just a name but a brand is an asset of the company. Prenagen Junior, a brand extension of Prenagen products for pregnancy and lactation, is a fictitious experiment in this study. The aim of the research was to analyze consumer attitudes towards brand extension. The method used pre-experiment_one shot case study. The population was taken from respondents who had used Prenagen products either Prenagen Esensis, Prenagen Emesis, Prenagen Mommy, or Prenagen Lactamom within last 6 months. A sample of 154 respondents was drawn from that population. The results obtained were analyzed using multiple regression analysis method. The results simultaneously showed that the similarity, brand reputation of origin, perceived risk, and innovativeness delivered a significant influence on consumers’ attitude towards brand extension (R2 : 0.556; p < 0.05). The similarity of brand extension product with the parent brand, the parent brand’s reputation, perceived risk had a significant influence by 20.8 %, 10.0 %, and 23.3 % respectively on the consumers’ attitude towards the brand extension product. While the innovativeness variable was not significant influence on that (B : 0.126 ; p > 0.05).Keywords: Brand Extension, Similarity, Reputation Of The Parent Brand, Perceived Risk, Innovativeness, Consumer Attitudes